2012
DOI: 10.1002/mus.23487
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of subjective clinical assessments of the patellar reflex

Abstract: These findings show that subjective assessments of reflexes using reflex rating scales correlate strongly with biomechanical and electromyographic measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Inter-rater variability in the clinical examination of the patellar tendon reflex has been resulted from the variability in the way clinicians elicit the reflex and assess the response [25]. In this study, the inter-rater variability was minimized using a standard elicitation method and the aid of an automatic assessment tool.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-rater variability in the clinical examination of the patellar tendon reflex has been resulted from the variability in the way clinicians elicit the reflex and assess the response [25]. In this study, the inter-rater variability was minimized using a standard elicitation method and the aid of an automatic assessment tool.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the common use and simplicity of DTR tests, however, clinical assessments of DTR responses remain subjective and qualitative [ 1 , 6 ]. Though some studies have evaluated the subjective assessment and concluded strong correlations with biomechanical and electromyographic measures, other studies have demonstrated low interrater reliability when assessing DTR responses [ 7 , 8 ]. Therefore, an opportunity exists to improve the widespread consistency and efficacy of these tests using quantitative methods.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have attempted to identify quantitative measures for improving the assessment of PTR tests, which is the focus of this study. The most common variables used to evaluate PTR responses are the first knee extension angle (FKEA) and the tendon reflex amplitude [ 7 , 9 ] which have both demonstrated to correlate well with subjective ratings of the NINDS and Mayo scales [ 7 ]. Measurements of angular velocity and acceleration, reflex latency, and movement latency have also been used to quantify PTR responses [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reflex response elicited by a tendon tap is usually referred to as a T-reflex (or phasic stretch reflex), while a reflex response obtained from an electrical stimulation to a mixed muscle nerve is known as an H-reflex [ 1 ]. The advantage of T-reflexes over H-reflexes is their routine use in clinical assessments of spinal cord integrity, since a basic mechanical percussion does not require any sophisticated apparatus [ 2 ]. Thus, it is generally easier (and cheaper) to deliver a mechanical percussion as compared to an electrical stimulation if a simple clinical hammer is used.…”
Section: Introductionmentioning
confidence: 99%